Supercritical carbonation treatment on extruded fibre-cement reinforced with vegetable fibres - Santos, Sérgio Francisco dos [UNESP]; Schmidt, Rene; Almeida, Alessandra Etuko Fuzikawa Souza; Tonoli, Gustavo Henrique Denzin; Savastano, Holmer (Elsevier B.V., 2015)
The objective of this research was to evaluate the effects of supercritical carbonation treatment for 2 h on the main hydrated phases of the cement matrix (calcium hydroxide and calcium silicate hydrate) and durability of extruded fibre-cement reinforced with bleached eucalyptus pulp and residual sisal chopped fibres. The thermal analysis, bulk density, porosity, physical characteristics and mechanical performance were evaluated before and after 200 soaking and drying cycles for following the degradation of the material under accelerated ageing conditions. The higher carbonation rate during the early stage of curing period decreased the porosity by sealing the opened pores around vegetable fibres and, consequently, led to lower water absorption and higher bulk density in the composites. The average MOR-values showed a significant increase in the case of the supercritical carbonated extruded fibre-cement in the initial age and after accelerated ageing. Besides, after 200 soaking and drying ageing cycles, the average values of energy of fracture (gamma WoF) of the carbonated composites decrease only 28%, showing evidences of the preservation of microstructural stability and toughness of the fibre-cement composites after supercritical CO2 treatment.
Keywords: Sisal fibre; Eucalyptus pulp; Extrusion; Energy of fracture; Fracture toughness; Supercritical carbon dioxide